2015
DOI: 10.3748/wjg.v21.i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation broadening its application beyond intestinal disorders

Abstract: Intestinal dysbiosis is now known to be a complication in a myriad of diseases. Fecal microbiota transplantation (FMT), as a microbiota-target therapy, is arguably very effective for curing Clostridium difficile infection and has good outcomes in other intestinal diseases. New insights have raised an interest in FMT for the management of extra-intestinal disorders associated with gut microbiota. This review shows that it is an exciting time in the burgeoning science of FMT application in previously unexpected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(161 citation statements)
references
References 112 publications
1
149
0
8
Order By: Relevance
“…Preclinical evidence demonstrating the modulatory effects of gut microbiota on the brain are primarily derived from 1) "germ-free" models where diseases are studied in animals devoid of microbial species, 2) models in which microbial manipulation is accomplished with antibiotics, and 3) models of fecal microbiota transplantation (FMT) 79,[83][84][85] . When examining this bottom-up influence of the GBMAx, evidence suggests the gut microbiota is mechanistically important for the regulation of central CNS processes.…”
Section: Gbmax: Linking the Gut And Neuroinflammationmentioning
confidence: 99%
“…Preclinical evidence demonstrating the modulatory effects of gut microbiota on the brain are primarily derived from 1) "germ-free" models where diseases are studied in animals devoid of microbial species, 2) models in which microbial manipulation is accomplished with antibiotics, and 3) models of fecal microbiota transplantation (FMT) 79,[83][84][85] . When examining this bottom-up influence of the GBMAx, evidence suggests the gut microbiota is mechanistically important for the regulation of central CNS processes.…”
Section: Gbmax: Linking the Gut And Neuroinflammationmentioning
confidence: 99%
“…Targeting the microbiota has resulted in improvement in a case study of a patient with Parkinson's disease and it has been shown that a full truncal vagotomy decreases the risk of the disorder as individuals enter old age (Gray et al, 2015). There are also case reports of improvement in patients with multiple sclerosis and autism following FMT (Xu et al, 2015). Proper controlled studies are clearly required.…”
Section: Microbiota Transplantationmentioning
confidence: 99%
“…In recent times we have seen a broadening of the indication for fecal microbiota transplantation (FMT) beyond the narrow remit of treating Clostridium difficile infection (Xu et al, 2015). Recently, a double blind trial of 18 patients with metabolic syndrome was reported.…”
Section: Microbiota Transplantationmentioning
confidence: 99%
“…Recent randomized controlled trials and a meta-analysis demonstrated a variable efficacy of FMT in IBD, especially for ulcerative colitis (7,9,10). The risk of IBD reactivation is still another worry, since a case of transient flare-up of ulcerative colitis after FMT has been reported (11).…”
Section: Discussionmentioning
confidence: 99%